Bridging School and Industry: A Correlational Study on Internship Experience and Custom Fashion Learning Outcomes - Febianti, Nur Sheila Ayu; Nurmasitah, Sita (Universitas Negeri Semarang, 2025)
Internship programs are mandatory in Indonesian vocational schools, including SMK Negeri 1 Kendal, to enhance students’ skills and work readiness. This study investigates the correlation between internship experience and learning outcomes in custom-made fashion production among 106 twelfth-grade fashion students. Using a quantitative correlational approach, data were collected through internship experience questionnaires and students’ competency exam scores. Statistical analysis via IBM SPSS 19 included validity and reliability tests, descriptive statistics, normality and linearity tests, and hypothesis testing using correlation and determination coefficients. Results showed a very weak and negative correlation (r = -0.126, p = 0.199), with only 1.6% of the variance in learning outcomes explained by internship experience. Although internships provided broad exposure to garment industry divisions, they did not significantly impact students’ performance in custom fashion making. This finding highlights a potential misalignment between internship content and curriculum goals, suggesting the need for program redesign and further in-depth research.